Lactate-to-Albumin Ratio (LAR) as a Predictor of Mortality in Sepsis Patients in the Intensive Care Unit at Dr. Hasan Sadikin General Hospital, Bandung. - maharani, geeta; Sujud, Reza Widianto; Erlangga, Erias (Faculty of Medicine, 2026)
Sepsis remains a major cause of mortality, particularly in developing countries, underscoring the need for simple, easily accessible biomarkers with strong prognostic value to facilitate early identification of high-risk patients in the ICU. The Lactate to Albumin Ratio (LAR) is an index that integrates information on metabolic stress through lactate levels and inflammation and nutritional status through serum albumin levels, offering the potential to serve as a more comprehensive prognostic marker than single parameters alone. This study aimed to evaluate the ability of LAR to predict mortality among septic patients admitted to the intensive care unit. A prospective cohort study was conducted involving 113 adult patients with sepsis treated in the ICU of Dr. Hasan Sadikin General Hospital, Bandung, throughout 2025. Within the first 24 hours of admission, serum lactate and albumin levels were measured to calculate the LAR, and patients were followed for 28 days to determine survival status. The findings demonstrated that the mean LAR was significantly higher in non-survivors than in survivors, with a cut-off value of 0.81 yielding a sensitivity of 81.0% and a specificity of 76.5% for predicting 28-day mortality. The area under the curve (AUC) of 0.86 indicated strong prognostic accuracy. These results suggest that LAR is significantly associated with mortality in septic patients in the ICU and may serve as a simple, cost-effective biomarker that can be easily incorporated into daily clinical practice to support risk stratification and guide management decisions in critically ill patients with sepsis.